Psycholinguistic, Stroop, and self-report measurements of death anxiety: A study of convergent validity. - Hollander, John; Dark-Freudeman, Alissa (Death Studies, 2023)
Death anxiety is commonly assessed using self-report surveys, but practitioners and researchers have recently established the need for implicit measures. However, many implicit measures lack sufficient evidence to support their construct validity. We examined two innovative implicit death anxiety measures (linguistic analysis and a Stroop paradigm) alongside a traditional self-report death anxiety survey battery. The linguistic analysis of death-related writing was supported by concurrent validity among death anxiety measures. We conclude that linguistic analyses of death-related writing may be a valid, viable, implicit measure of death anxiety which may be useful to both researchers and clinicians.